Huzurevinde Kalan Yaşlıların Minnettarlık, Mental İyi Oluş ve Öz Anlayış Düzeyleri Üzerine Bir Alan Araştırması - Demirci, Yunus Emre; Anlı, Gazanfer (Hacettepe Üniversitesi, 2022)
Bu araştırmanın amacı, huzurevinde kalan yaşlıların minnettarlık, mental iyi oluş ve öz-anlayış düzeyleri arasındaki ilişkiyi incelemektir. Bu amaç doğrultusunda, yaşlıların minnettarlık ve öz-anlayış düzeylerinin mental iyi oluşlarını yordayıp yordamadığı sorusuna yanıt aranmaktadır Ayrıca araştırmada, minnettarlık, mental iyi oluş ve öz-anlayış düzeylerinin cinsiyet, yaş ve huzurevinde kalma süresi değişkenliği incelenmiştir. Bu araştırmada nicel yönteme dayalı olarak ilişkisel tarama modeli kullanılmıştır. Araştırma Bursa Büyükşehir Belediyesi Huzurevi’nde yaşayan 120 yaşlı ile yapılmıştır. Örneklemi 22’si kadın 98’i erkek oluşturmaktadır. Araştırmada veri toplama araçları olarak Minnettarlık Ölçeği, Warwick Edinburg Mental İyi Oluş Ölçeği, Öz-Anlayış Ölçeği ve Kişisel Bilgi Formu kullanılmıştır. Araştırma sonucunda minnettarlık, mental iyi oluş ve öz-anlayış düzeyleri arasında anlamlı ilişkiler olduğu belirlenmiştir. Ayrıca minnettarlık ve öz-anlayış düzeylerinin mental iyi oluş düzeyini yordadığı ve %33,5’sini açıkladığı bulunmuştur. Minnettarlık, mental iyi oluş ve öz-anlayış düzeylerinin cinsiyet, yaş ve huzurevinde kalma süresi açısından farklılaşmadığı tespit edilmiştir.

The aim of this research is to examine the relationship between gratitude, mental well-being and self-compassion levels of the elderly residents in nursing home. In accordance with this aim what extent gratitude and self-compassion levels of the elderly that predicted the mental well-being was answer the question. Also, this study analyzed the relationship between the gratitude, mental well-being and self-compassion levels and gender, age and length residence in nursing home. This study used to quantitative method based relational scanning model. The research was contucted with 120 elderly residing at Bursa Metropolitan Municipality Nursing Home. The sample consisted of 22 women elderly and 98 men elderly. As a data collection tools, Gratitude Scale, WEMWB Scale, Self-Compassion Scale and Basic Personal Information Form were used in the study. As result, it was found that there are relationships between gratitude, mental well-being and self-compassion levels. In addition, it was found that gratitude and self-compassion levels predicted mental well-being and explained %33.5 of it. It was found that gratitude, mental well-being and self-compassion levels did not differ in terms of gender, age and duration of stay in nursing home.
A Field Research on Gratitude, Mental WellBeing and Self-Compassion Level of Elderly Individuals in Nursing Home
Keywords: Sociology (Other); Sosyoloji (Diğer)